Healthcare Facilities in Emerging Countries The Challenge for India (PoliMI SpringerBriefs, 2018)
This multidisciplinary book brings together medical, management, and architectural disciplines in order to formulate new approaches to the programming, planning, and design of healthcare facilities that will improve the quality of healthcare systems in rapidly developing countries, respecting local culture. It achieves this aim by drawing upon case studies on healthcare facilities and services that were undertaken in Kolkata, India, where the public healthcare system is meager and most people do not have access to health services. The approaches presented pay appropriate attention to technical aspects and organizational set-up and are designed to achieve an adequate healthcare assistance, greater production efficiency, better use of local professional resources, and careful control of construction. They are also intended to promote educational progress and future independence in construction and management of the healthcare system. The book will appeal to all with an interest in design and organizational strategies to meet new healthcare challenges in India and other emerging countries.